ANALISIS PENGAMBILAN KEPUTUSAN MASYARAKAT DALAM MEMILIH JASA PINJAMAN DI BANK BRI KCP TINANGGEA - Tonasa, Muhamad; Elvirawati, Elvirawati (Institut Teknologi dan Bisnis Kristen Bukit Pengharapan, 2024)
This research aims to describe the customer decision process in choosing loan services at Bank BRI Tinanggea, factors that influence customers' decisions in choosing loan services at Bank BRI Tinanggea. To analyze the Islamic Legal Basis for making loans at conventional banks. This research is descriptive qualitative research. In collecting data, the author used primary data sources, namely taken from observations and interviews, other documentation and tertiary data in the form of dictionaries, and information from the internet. The research results show that there are three factors that influence customers to choose BRI Tinanggea bank as a loan service, namely, social factors, personal factors and psychological factors. The most dominant factor influencing customers to choose BRI Tinanggea Bank as a loan service is personal (economic) factors.